2014
DOI: 10.1021/ie403239s
|View full text |Cite
|
Sign up to set email alerts
|

PVDF Latex As a Binder for Positive Electrodes in Lithium-Ion Batteries

Abstract: The present work shows a way to develop an industrial organic solvent-free process for lithium-ion battery electrodes manufacturing. The process uses a water-based slurry to cast the electrodes, using poly vinylidene-fluoride (PVDF) as a polymeric binder. The use of aqueous PVDF latex as a binder in positive electrodes is of difficult integration in existing production lines due to the low stability of lithium cobalt oxide (LiCoO2) in an aqueous environment. The use of electroless plating solves this issue by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 17 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…Different polymers like polyvinylidene fluoride (PVDF), copolymers of vinylidene fluoride (VDF), and trifluoroethylene are semicrystalline polymers and have both pyro-and piezoelectric properties (Kang and Cao, 2014;Liang et al, 2014;Spreafico et al, 2014). They are increasingly being used as electro-thermal and electromechanical transducer or sensors with promising medical and industrial applications (Dongliang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Different polymers like polyvinylidene fluoride (PVDF), copolymers of vinylidene fluoride (VDF), and trifluoroethylene are semicrystalline polymers and have both pyro-and piezoelectric properties (Kang and Cao, 2014;Liang et al, 2014;Spreafico et al, 2014). They are increasingly being used as electro-thermal and electromechanical transducer or sensors with promising medical and industrial applications (Dongliang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Among these aqueous binders carbomethyl cellulose and other biopolymers, poly(acrylic acid), SBR latexes, and poly(ethylene oxide) (PEO) were the most successful ones . It is worth to note that some companies have also developed PVDF aqueous formulations to be used as binders …”
Section: Polymer Separators and Bindersmentioning
confidence: 99%
“…[5] It is worth to note that some companies have also developed PVDF aqueous formulations to be used as binders. [6] An even more interesting approach is to use binders that have an active functional role in the electrode. To this end, several works reported the use of conducting polymers such as PEDOT/PSS or other polythiophenes in different electrode formulations.…”
Section: Role Of Polymers In Batteriesmentioning
confidence: 99%
“…However, the problem with water as the solvent is the degradation of lithium cobalt oxide (LCO) in aqueous condition . Spreafico et al . reported a PVDF latex as binder for LCO.…”
Section: Introductionmentioning
confidence: 99%
“…However, the problem with water as the solvent is the degradation of lithium cobalt oxide (LCO) in aqueous condition. [27] Spreafico et al [28] reported a PVDF latex as binder for LCO. Other water-soluble polymers, such as, b-cyclodextrin, [29] poly(acrylamide-co-diallyl dimethylammonium chloride) , [30] and water-soluble elastomer binder (e. g. styrene butadiene rubber, SBR) from ZEON Corp., [31] were also studied mostly for anode materials, such as graphite and silicon.…”
Section: Introductionmentioning
confidence: 99%